The Have an Impact on of Management Style and Paintings Motivation on Job Satisfaction and Worker overall Performance (HR Literature Review) - Kurniasih, Gusmi (Dinasti International Journal of Digital Business Management, 2022)
Literature article Reviewing the impact of management style and paintings Motivation on job delight and employee overall performance is a systematic article that goals to construct a studies speculation at the affect among variables a good way to be utilized in similarly research, in the scope of Human sources management. The approach of scripting this Literature assessment article is the library studies approach, which is sourced from on line media along with Google student, Mendeley, and other educational online media. The effects of this Literature evaluation article are: 1) management fashion has an impact on activity satisfaction; 2) paintings Motivation has an effect on activity delight; 3) management fashion has an impact on employee overall performance; four) paintings Motivation has an impact on worker performance, and 5) activity pleasure has an effect on employee performance.